PREVALENSI PENDERITA DEMAM BERDARAH DENGUE DI PUSKESMAS SIBIRU-BIRU KEC. SIBIRU-BIRU SUMATERA UTARA TAHUN 2014-2016 - Wijaya, Moses; Pasaribu, Sumihar M; Tiji, Widjaya Taufik (Jurnal Kedokteran Methodist, 2020)
Background: Dengue Haemorrhagic Fever (DHF) is an acute epidemic disease caused bya virus that is transmitted by Aedes aegypti and Aedes albopictus. According to the resultsof the Provincial Health Department report Sumut years 2014, Deli Serdang District is thenumber of patients with DHF majority votes in compare other districts in the province ofNorth Sumatra. This research aims to know the prevalence of patients with DHF in thePublic Health Center Sibiru-Biru, Sibiru-Biru Sub-district, North Sumatra in 2014-2016.Methods: The sampling technique in this study is total sampling with a sample of 56people. The collection of data is done by using the secondary data from medical recordson patients with DHF in the Public Health Center Sibiru-Biru.Results: Based on the research has been done about the prevalence of patients with DHFin Public Health Center Sibiru-Biru, Sibiru-Biru Sub-district, North Sumatra in 2014-2016. Show that from 56 patients who came for treatment, obtained groups of gender themost suffered DHF is women namely 32 people (57.1%), age groups the most sufferedDHF is the age of 11-20 years namely 13 people (23.2%) and 56 samples examined, thereare 2 samples (3.6%) who have a history of previous DHF and 54 samples (96.4%) thatdoes not have a history of previous DHF.Conclusion: Based on the study it can be concluded that in patients with DHF in thePublic Health Center Sibiru-Biru, Sibiru-Biru Sub-district, North Sumatra in 2014-2016top is gender women, age 11-20 years and the The highest prevalence rates of patientswith DHF in the Public Health Center Sibiru-Biru, Sibiru-Biru Sub-district, North Sumatrain 2014-2016: 0.1449%.